Early Brain microRNA/mRNA Expression is Region-Specific After Neonatal Hypoxic-Ischemic Injury in a Mouse Model - Peeples, Eric S.; Sahar, Namood-e; Snyder, William; Mirnics, Karoly (Frontiers in Genetics, 2022)
Background: MicroRNAs (miRNAs) may be promising therapeutic targets for neonatal hypoxic-ischemic brain injury (HIBI) but targeting miRNA-based therapy will require more precise understanding of endogenous brain miRNA expression. Methods: Postnatal day 9 mouse pups underwent HIBI by unilateral carotid ligation+hypoxia or sham surgery. Next-generation miRNA sequencing and mRNA Neuroinflammation panels were performed on ipsilateral cortex, striatum/thalamus, and cerebellum of each group at 30 minutes after injury. Targeted canonical pathways were predicted by KEGG analysis. Results: Sixty-one unique miRNAs showed differential expression (DE) in at least one region; 9 in more than one region, including miR-410-5p, -1264-3p, 1298-5p, -5126, and -34b-3p. Forty-four mRNAs showed DE in at least one region; 16 in more than one region. MiRNAs showing DE primarily targeted metabolic pathways, while mRNAs targeted inflammatory and cell death pathways. Minimal miRNA-mRNA interactions were seen at 30 minutes after HIBI. Conclusions: This study identified miRNAs that deserve future study to assess their potential as therapeutic targets in neonatal HIBI. Additionally, the differences in miRNA expression between regions suggest that future studies assessing brain miRNA expression to guide therapy development should consider evaluating individual brain regions rather than whole brain to ensure the sensitivity needed for the development of targeted therapies.